Teacher Educators’ Conceptualisation of Global Citizen - Shar, Noor Hussain; Chang, Ali Gohar; Siyal, Ayaz Latif (Annals of Human and Social Sciences, 2023)
Adopting Interpretative Psychological Analysis (IPA) in qualitative research, this paper examines the conceptualisation of Global Citizenship (GC) by teacher educators in a public sector University in Pakistan. The research focuses on two of the three dimensions of GC suggested by UNESCO, (2015), i.e. cognitive and socio-emotional. Data was collected through semi-structured interviews. The findings reveal that teacher educators conceptualise GC in their own ways and there is no one agreed definition of it. The participants conceptualise GC as individual identity, awareness of global issues, and interconnectedness with the world. Moreover, they view a global citizen as a part of a community that extends beyond a nationstate. The participants believe that pluralistic thinking and respect for diversity and social media are enablers of global citizenship. Keeping in view a narrow conceptualisation of global citizenship this research recommends learning experience if GC education is made part of teacher education programmes in the country.